Unrestricted interpretation of German civil law during the National Socialism period - Đorđević Slavko; Pirner Štefan (Anali Pravnog Fakulteta u Beogradu)
When the Nazis came to power in 1933, they began to rebuild the German legal system in accordance with the National Socialism ideology. Considering it was impossible to complete this task "overnight", the Nazi legal theory established the view that all acts and statutes enacted prior to 1933 must be interpreted in the interest of National Socialism. In this paper the authors analyse the theoretical foundations of such interpretation, which was marked as "unrestricted interpretation of law" in post-war legal theory, focusing on its role in the process of Nazification of German civil law that was actively practiced by German courts. The authors also briefly analyse the post-war process of "denazification" of the laws enacted during the Nazi era, which was also performed by the mean of legal interpretation, but this time with the aim of eliminating the Nazi ideology from legal rules.